2000
DOI: 10.1902/jop.2000.71.10.1535
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Interleukin‐1β, ‐8, and ‐10 and RANTES in Gingival Crevicular Fluid and Cell Populations in Adult Periodontitis Patients and the Effect of Periodontal Treatment

Abstract: These data suggest that the amount of crevicular IL-1 beta, IL-8, and IL-10 and RANTES is associated with periodontal status. Removal of the bacterial plaque reduces the antigenic stimuli and consequently could modulate the chemokines present in GCF. We propose that the dynamic interactions between cytokines, their production rates, and their quantity could represent factors controlling the induction, perpetuation, and collapse of the cytokine network present in the periodontal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
288
4
13

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 314 publications
(328 citation statements)
references
References 58 publications
23
288
4
13
Order By: Relevance
“…Chemokines such as IL-8 and MCP-1 may be related to periodontitis severity (7,28). Previously, several investigators have shown that chemokine levels in gingival crevicular fluid decrease after periodontal therapy (7,12).…”
Section: Chemokinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemokines such as IL-8 and MCP-1 may be related to periodontitis severity (7,28). Previously, several investigators have shown that chemokine levels in gingival crevicular fluid decrease after periodontal therapy (7,12).…”
Section: Chemokinesmentioning
confidence: 99%
“…Previously, several investigators have shown that chemokine levels in gingival crevicular fluid decrease after periodontal therapy (7,12). Thus, chemokines seem to be attractive therapeutic targets for periodontitis management.…”
Section: Chemokinesmentioning
confidence: 99%
“…Gamonal et al (14,18) determinaron mayores niveles de CCL5 en sitios que presentaron actividad periodontal (47.02 pg/ 49.64 pg/µL) después de 2 meses de seguimiento comparados con sitios que no evidenciaron actividad en el mismo paciente (37.55 pg/47.53 pg/µL), datos que coinciden con el presente estudio para sitios periodontalmente comprometidos frente a sitios sanos. Sin embargo, los resultados discrepan con otros estudios (19)(20)(21) en cuanto a los niveles reportados para los sitios control, en los que se observó una cuantificación hasta 50% mayor en los niveles de CCL5.…”
Section: Discussionunclassified
“…Mientras los linfocitos Th1 son considerados la mayor fuente de RANK-L, molécula potencialmente inductora para la activación de los osteoclastos en las patologías periodontales, las células dendríticas y macrófagos son potenciales precursores de osteoclastos, reforzando el rol de ésta en la pérdida ósea (14,15). CCL5 se ha encontrado específicamente en tejidos periodontales de sujetos periodontalmente comprometidos, comparados con controles, y su concentración disminuye en el líquido crevicular después de aplicada la terapéutica periodontal.…”
Section: Introductionunclassified
“…IL-1 and TNF-α induce cells to produce CRP. In a number of studies, proinflammatory cytokines in gingival crevicular fluid and in inflamed gingival tissues were reported in a high amount at patients with active periodontal disease to the healthy group 6 . In another research, acute phase proteins, including CRP, has been found at increased levels in gingival crevicular fluid 7,8 .…”
Section: Introductionmentioning
confidence: 99%